Protecting the Union: Analysing an Emerging Policy Space - Boin, Arjen; Ekengren, Magnus; Rhinard, Mark (Journal of European Integration, 2006)
Recent organizational, institutional and policy developments signal a new type of co-operative policy activity at the European level and suggest the emergence of a new policy space in the European Union. What binds together the activities in that space is a common concern for the protection of the EU citizen. This new policy space crosses sectoral boundaries, draws in a number of governmental and societal actors, and comprises a variety of institutional venues. Moreover, its dimensions span the internal and external divide in EU policies. This article serves as an introduction to a special issue on the topic of the EU's emerging protection policy space. It first discusses the empirical parameters of this emerging space, before outlining a set of research questions and surveying the theoretical landscape for addressing these questions. It concludes by introducing the articles that comprise the special issue.